Towards the co-production of urban space for increased inclusiveness. Case study: Holzmarkt Berlin. - Humann, Melanie (My University, 2020)
Increasingly, civil society is demanding greater participation and involvement in urban development. For this reason, planning processes have become more openly structured in recent years, offering a wider range of opportunities for participation. In order to enable such participation not only in planning but also in producing the city itself, structures for the co-production of urban space have now established themselves. The co-productive city is being made reality by civil society and local actors, whose goal is to create a long-term and sustainable value creation chain. As a counter-model to the neoliberal city, co-productive urban development requires alternative financial and organizational structures. Here our primary focus is the community-based and inclusive production of space that also redefines the role of the planner.
Keywords: Stadtplanung; Stadtentwicklungsplanung; Partizipation; Planungskooperation; Bewohnerbeteiligung; Planungsbeteiligung; Inklusion